2020
DOI: 10.31235/osf.io/udzah
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A discussion of irrational stockpiling behaviour during crisis

Abstract: One of the ubiquitous human behaviours observed in natural disasters and humanitarian crisis is irrational stockpiling (also known as hoarding or panic buying). Limited, distorted and exaggerated information during crisis disturbs people’s judgement and results in aberrant actions which can be explained with economics and psychology theories. The objective of this paper is to examine the perplexing stockpiling phenomena during disasters like COVID-19 pandemic and discuss its immediate and long-term impact on e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 2 publications
0
26
0
Order By: Relevance
“…Perceived scarcity has been mentioned repeatedly by different groups of authors as an important responsible factor for PB ( 2 , 6 , 7 ). However, perception of threat and/or perception of risk have also been mentioned as a factor that has not been found in the current study ( 3 , 7 ).…”
Section: Discussionmentioning
confidence: 94%
See 4 more Smart Citations
“…Perceived scarcity has been mentioned repeatedly by different groups of authors as an important responsible factor for PB ( 2 , 6 , 7 ). However, perception of threat and/or perception of risk have also been mentioned as a factor that has not been found in the current study ( 3 , 7 ).…”
Section: Discussionmentioning
confidence: 94%
“…The study revealed that PB has been reported in 93 countries. Previous studies reported the distribution of the countries; however, none of the studies mentioned such wide distributions ( 1 , 2 , 4 , 5 ).…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations